EFFECT OF LOCATION IN TRANSVERSE PLANE FOR 45-DEGREE V-BAFFLE ON FLOW AND HEAT TRANSFER MECHANISMS IN A SQUARE CHANNEL - Withada Jedsadaratanachai; Amnart Boonloi (My University, 2018)
A premiere free-access and peer-reviewed frontier journal site, serving the needs of the thermal-fluids community. See the latest research or submit an article. Quickly share your research with the global thermal-fluids community, for increased citations and impact at no cost.
Keywords: Thermal fluids; Baffle; Square (algebra); Frontier; Degree (music); Heat Transfer and Boiling Studies